A New Method for Chromosomes Preparation by ATP-Competitive Inhibitor SP600125 via Enhancement of Endomitosis in Fish - Xu, Wenting; Mo, Yanxiu; He, Yu; Fan, Yunpeng; He, Guomin; Fu, Wen; Chen, Shujuan; Liu, Jinhui; Liu, Wenbin; Peng, Liangyue; Xiao, Yamei (Frontiers in Bioengineering and Biotechnology, 2021)
Previous studies have suggested that 1,9-Pyrazoloanthrone, known as SP600125, can induce cell polyploidization. However, what is the phase of cell-cycle arrest caused by SP600125 and the underlying regulation is still an interesting issue to be further addressed. Research in this article shows that SP600125 can block cell-cycle progression at the prometaphase of mitosis, and cause endomitosis. It is suggested that enhancement of the p53 signaling pathway and weakening of the spindle assembly checkpoint are associated with the SP600125-induced cell cycle arrest. Using preliminary SP600125 treatment, the samples of the cultured fish cells and the fish tissues display a great number of chromosome splitting phases. Summarily, SP600125 can provide a new protocol of chromosomes preparation for karyotype analysis owing to its interference with prometaphase of mitosis